Integrated network pharmacology and DSS-induced colitis model to determine the anti-colitis effect of Rheum palmatum L. and Coptis chinensis Franch in granules. (10th January 2023) - Yan, Wenxin; Feng, Qian; Li, Yu; Lin, Yuefang; Yao, Jingjing; Jia, Zhen; Lu, Linlin; Liu, Liang; Zhou, Hua
Abstract: Ethnopharmacological relevance: Rheum palmatum L. (RP) and Coptis chinensis Franch. (CC), frequently used as herbal pair (HP) in clinical practicing of traditional Chinese medicine, exerted predominate efficacies in colitis treatment. However, the mechanism of their synergism lacks scientific explanation. Aim of the study: By integrating network pharmacology and DSS-induced colitis model, the anti-colitis effects and synergistic molecular mechanisms of RP-CC combination was determined. Materials and methods: In vivo study, mice were divided into control, model, RP, CC and RP-CC (low, middle, high) groups, 2.5% DSS was administrated to induce colitis for consecutive 7 days, subsequently, the therapeutic effects were evaluated from body weight changes, disease activity index (DAI), and pathological conditions. After determining the shared and exclusive targets of RP and CC, respectively by network pharmacology, CETSA, WB, and qPCR were utilized to verify the action modes of RP and CC on specific targets. Results: Compared to RP or CC used alone, RP-CC combination can significantly protect colon tissues from inflammatory damage in a dose-dependent manner via remarkably alleviating DAI and colon shortening. Network pharmacological analysis suggested that AKT1 would be the core target for RP-CC synergism since these two herbs could simultaneously but non-competitively bind to AKT1 at different sits. Furthermore, RP and CC could also influencing HIF and MAPK pathways, respectively, these additional actions attribute to more optimizing effectiveness towards colitis. Conclusion: In contrast to the mild therapeutic effects of RP or CC individually, RP-CC herb pair could exert strong and synergistic effects in treatment of colitis via non-competitive binding to AKT1 simultaneously, as well as exclusively influencing MAPK and HIF pathways. Our study not only provides the evidence for understanding the combined effect of RP and CC, but also brings up a new strategy and suggestive thoughts for the rationality of HP-based TCM formula. Graphical abstract: Image 1 Highlights: Rheum palmatum L. (RP) and Coptis chinensis Franch. (CC) had synergistic effects treating colitis when used in combination. Components of RP and CC can non-competitively bind to AKT1, exerted anti-inflammatory effects. Crosstalk among MAPK, HIF1 signaling pathway could be the novel mechanism for synergism of RP-CC herb pair.